Synthesis and characterization of WS₂ inorganic nanotubes with encapsulated/intercalated CsI - Hong, S; Popovitz-Biro, R; Tobias, G; Ballesteros, B; Davis, B; Green, M; Tenne, R (Springer, 2010)
WS₂ nanotubes have been filled and intercalated by molten phase caesium iodide. The presence of caesium iodide inside the WS₂ nanotubes has been determined using high-resolution transmission electron microscopy (HRTEM) coupled with electron energy-loss spectroscopy (EELS) and energy-dispersive X-ray spectroscopy (EDS). Noticeably, a Moiré pattern was observed due to the interference between encapsulated CsI and WS₂ layers. The intercalation of CsI into the host concentric WS₂ lattices resulted in an increase in the interplanar spacing.